2002
DOI: 10.1016/s0925-8388(01)01580-8
|View full text |Cite
|
Sign up to set email alerts
|

Effect of reactive mechanical grinding on chemical and hydrogen sorption properties of the Mg+10 wt.% Co mixture

Abstract: :Reactive mechanical grinding (MG under H 2 ) of magnesium powder improves the hydrogen sorption properties. The hydrogenation of Mg starts in situ during the milling process that allows suppressing the activation procedure generally requested for Mg. The addition of Co, which acts as a catalyst for the dissociation of H 2 , also leads to an improvement of the hydrogen sorption properties (but a strong dependence upon the milling time is reported). The hydriding is determined to be a two-step process: nucleati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
25
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(27 citation statements)
references
References 17 publications
2
25
0
Order By: Relevance
“…Unfortunately, the application is primarily limited by the high hydrogenation reaction temperature and slow kinetics [4][5]. Experimentally, a number of studies have been devoted to the catalytic effect on hydrogen adsorption of mixing transition metals into the Mg powder by mechanical milling [6][7][8]. Apart from metallic alloying, some non-metallic elements such as graphitic carbon have been noted to facilitate the activation process of Mg and improve the absorption kinetics of H 2 [9][10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…Unfortunately, the application is primarily limited by the high hydrogenation reaction temperature and slow kinetics [4][5]. Experimentally, a number of studies have been devoted to the catalytic effect on hydrogen adsorption of mixing transition metals into the Mg powder by mechanical milling [6][7][8]. Apart from metallic alloying, some non-metallic elements such as graphitic carbon have been noted to facilitate the activation process of Mg and improve the absorption kinetics of H 2 [9][10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…Reactive mechanical milling of Mg and 10 wt.% Co has been shown to result in improvement of hydrogen sorption properties [82]. The rate of formation of MgH 2 at 350°C was fairly constant in the initial stages and decreased in the later stages (Fig.…”
Section: Magnesium Hydride and Its Nanostructuresmentioning
confidence: 95%
“…For example, Bobet et al [82,[122][123][124] synthesized MgH 2 via RMA at room temperature and studied the influence of addition of 3d-metals on the synthesis. It was observed that addition of 10 wt.% Co as a catalyst increased the yield of MgH 2 to 71% after 10 h of milling.…”
Section: Magnesium Hydride and Its Nanostructuresmentioning
confidence: 99%
“…This inhomogeneity is directly associated with the chemisorption of hydrogen and hence facilitates the hydriding reaction. The catalytic effect of Co has been well elaborated by Bobet et al [27]. Ni is a largely known catalyst, which is utilized for the hydriding reactions.…”
Section: Gaseous and Electrochemical Hydriding And Dehydriding Kineticsmentioning
confidence: 99%